Godzilla - Michael Sorkin (Oz, 1994)
I have never been to Tokyo and decided a couple of years ago that before my delirious vision of the place was contaminated by the cruel and contorting rigors of actual observation, I'd better do a project there; we're still working on it. Although this building has come to be known as Godzilla around the studio, I don't mean it to be sinister, just large, a building with—shall we say—presence.